RUSSIAN LANGUAGE FOR TRAVELERS: POPULAR PHRASES - Farrukh Bakhramovich Khakimov (World Scientific Research Journal, 2025)
Annotation: The Russian language is not only a language with a rich history and culture, but also a language that can be extremely useful for travelers. Knowing even the most basic phrases will help you feel confident in Russia and other Russian-speaking countries. This article will provide an in-depth look at key phrases and expressions that will be needed in everyday situations, such as communicating with locals, buying tickets, ordering food, and various ways to ask for help. This article will be useful for both beginners and those who want to improve their knowledge of the Russian language before traveling.